Divine foreknowledge and providence in the commentaries of Boethius and Aquinas on the De interpretatione 9 of Aristotle - Torrijos-Castrillejo, David (Biblica et Patristica Thoruniensia, 2020)
Boethius represents one of the most important milestones in Christian reflection about fate and providence, especially considering that he takes into account Proclus’ contributions to these questions. For this reason, TheConsolation of philosophy is considered a crucial work for the development of this topic. However, Boethius also exposes his ideas in his commentary on the book that constitutes one of the oldest and most relevant texts on the problem of future contingents, namely Aristotle’s De interpretatione. Although St. Thomas refers to Boethius many times in his systematic works and even devotes two commentaries to two of his theological opuscules, it is of special interest that both authors composed a commentary on the abovementioned work of Aristotle. The commentary of Saint Thomas does not interpret the whole book, but it does study the pages about future contingents in dialogue with Boethius. We will study such texts in our presentation. They constitute one of the greatest contributions of Aquinas to the problem of necessity and contingency and therefore to the vexata quaestioof divine intervention in the world and particularly in human free will. Not only Augustin but also Aristotle (read by Boethius) and Nemesius of Emesa will be decisive in Aquinas’ perception of this matter.